Importance of electrostatic effects for interpretation of X-ray photoemission spectra of self-assembled monolayers - Zharnikov, Michael (Advanced materials interfaces, 2025)
This paper reviews the relevant work regarding electrostatic effects in X-ray photoemission from self-assembled monolayers (SAMs) which are application-relevant ultrathin molecular films, coupled over a suitable anchoring group to the substrate. Whereas, in most cases, the standard concept of chemical shift is fully sufficient to describe X-ray photoelectron spectra of these systems, consideration of electrostatic effects is frequently necessary for their proper interpretation. Due to the insulator character of the SAM matrix, decoupled electronically from the substrate, the introduction of a dipolar ´sheet´ at the SAM-substrate interface or within this matrix creates a potential discontinuity shifting the energy levels above the ´sheet´ with respect to those below it. This shift is reflected then in the matrix-related spectra, resulting in shifts and splitting of the characteristic photoemission peaks. Several representative examples in this context are provided and discussed in detail. These examples and other relevant literature data underline the importance of electrostatic effects in photoemission and suggest that they should be considered on the equal footing as the chemical shift ones.